The research of OAM dielectric resonator array antenna - Chang Wei; Sun Xuehong; Liu Liping; Xue Jianan (Dianzi Jishu Yingyong, 2018)
Orbital angular momentum(OAM) technology provides a new modulation dimension for wireless communication system, and it has become an effective way to solve the problem of spectrum resource shortage. A novel OAM array antenna is proposed in this paper, which uses a dielectric resonator array antenna to produce a OAM beam. The simulation results show that the OAM antenna array radius affects the OAM beam effect, the suitable feeding position and feeding mode can ameliorate the central space problem and improve the quality of long-distance transmission of OAM beam. This OAM array antenna has the advantages of small volume and wide selection of dielectric materials, it can solve the problem of the ring-shaped OAM microstrip array antenna, which is the high loss of the high frequency band and the large size of the low frequency band. It provides a new reference value for the practical application of OAM array antenna in the field of wireless communication.